Contrasting vector competence of three main East African Anopheles malaria vector mosquitoes for Plasmodium falciparum - Prisca A. Kweyamba; Lorenz M. Hofer; Ummi A. Kibondo; Rehema Y. Mwanga; Rajabu M. Sayi; Fatuma Matwewe; Dickson W. Lwetoijera; Mgeni M. Tambwe; Sarah J. Moore (Scientific Reports)
Abstract There are three Anopheles mosquito species in East Africa that are responsible for the majority of malaria transmission, posing a significant public health concern. Understanding the vector competence of different mosquito species is crucial for targeted and cost-effective malaria control strategies. This study investigated the vector competence of laboratory reared strains of East African An. gambiae sensu stricto, An. funestus s.s., and An. arabiensis mosquitoes towards local isolates of Plasmodium falciparum infection. Mosquito feeding assays using gametocytaemic blood from local donors revealed significant differences in both prevalence and intensity of oocyst and sporozoite infections among the three vectors. An. funestus mosquitoes presented the highest sporozoite prevalence 23.5% (95% confidence interval (CI) 17.5–29.6) and intensity of infection 6-58138 sporozoites. Relative to An. funestus, the odds ratio for sporozoites prevalence were 0.46 (95% CI 0.25–0.85) in An. gambiae and 0.19 (95% CI 0.07–0.51) in An. arabiensis, while the incidence rate ratio for sporozoite intensity was 0.31 (95% CI 0.14–0.69) in An. gambiae and 0.66 (95% CI 0.16–2.60) in An. arabiensis. Our findings indicate that all three malaria vector species may contribute to malaria transmission in East Africa, with An. funestus demonstrating superior vector competence. In conclusion, there is a need for comprehensive malaria control strategies targeting major malaria vector species, an update of malaria transmission models to consider vector competence and evaluation of malaria transmission blocking interventions in assays that include An. funestus mosquitoes.